2018
DOI: 10.1126/scitranslmed.aao3089
|View full text |Cite
|
Sign up to set email alerts
|

Platelet microparticles sustain autophagy-associated activation of neutrophils in systemic sclerosis

Abstract: Endothelial cell damage and platelet activation contribute to sustained vasculopathy, which is a key clinical characteristic of systemic sclerosis (SSc), also known as scleroderma. Microparticles released from activated platelets in the blood of SSc patients (SSc-microparticles) are abundant and express the damage-associated molecular pattern (DAMP) HMGB1. SSc-microparticles interacted with neutrophils in vitro and in immunocompromised mice and promoted neutrophil autophagy, which was characterized by mobiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(160 citation statements)
references
References 71 publications
6
154
0
Order By: Relevance
“…Microparticles were derived from platelets and expressed the damage-associated molecular pattern HMGB1. An inhibitor of HMGB1 attenuated neutrophil activation [131] Natural killer A peculiar natural killer cell phenotype in SSc patients was identified characterized by decreased chemokine and activation receptors expression. These SSc-derived natural killer cells were potent inducers of endothelial microparticle release suggesting that there may be a role for natural killer cells in the activation of endothelial cells in SSc [133] Innate lymphoid Type 2 innate lymphoid (ILC2) cells are elevated in patients with SSc.…”
Section: Resultsmentioning
confidence: 99%
“…Microparticles were derived from platelets and expressed the damage-associated molecular pattern HMGB1. An inhibitor of HMGB1 attenuated neutrophil activation [131] Natural killer A peculiar natural killer cell phenotype in SSc patients was identified characterized by decreased chemokine and activation receptors expression. These SSc-derived natural killer cells were potent inducers of endothelial microparticle release suggesting that there may be a role for natural killer cells in the activation of endothelial cells in SSc [133] Innate lymphoid Type 2 innate lymphoid (ILC2) cells are elevated in patients with SSc.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms behind the movement of cytoplasmic HMGB1 out of the cell, however, are much less well understood, and may be cell, tissue, and stimulus dependent. Active secretion of HMGB1 has been shown to occur via exocytosis of HMGB1‐containing secretory lysosomes, microparticles, and exosomes . However, the details of the signaling pathways leading to HMGB1 exocytosis, including targeting to specific vesicles, remain elusive.…”
Section: Getting Hmgb1 Out Of Cells and Into The Circulationmentioning
confidence: 99%
“…For example, HMGB1 has been shown to cause vascular barrier dysfunction and accumulation of neutrophils (Nawaz & Mohammad, ). Based on a recent publication showing that platelet‐derived MPs from patients with systemic sclerosis express high levels of HMGB1 (Maugeri et al, ), we asked, in our experiments, whether neutrophil‐derived MPs also contain HMGB1. By using transmission immunoelectron microscopy, we found that neutrophil‐derived MPs attached to NETs express HMGB1.…”
Section: Discussionmentioning
confidence: 99%